ANALYSIS OF THE LEVEL OF KNOWLEDGE AND COMPLIANCE ON THE USE OF ANTIBIOTICS IN WIROKERTEN VILLAGE COMMUNITIES - Rissa, Mexsi Mutia; Nafisah, Risky (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Gombong, 2023)
Based on the results of Basic Health Research in 2013, people store antibiotics by 27.8%. Storage of hard drugs and antibiotics for self-medicating indicates irrational use of the drug. As many as 86.1% of households keep antibiotics obtained without a prescription. Lack of knowledge about the use of antibiotics has an effect on people's compliance. The purpose of this study was to determine the relationship between the level of public knowledge and compliance with the use of antibiotics in the hamlet of Wirokerten Banguntapan Bantul. The research method use is analytical observational with a cross sectional approach. The respondents in this study were 311 with a sample of 76 respondents. The data normality test uses the Kolmogorov-smirnov test. The results obtained were processed and analyzed using SPSS 23 with the Chi Square fisher test to determine the relationship between knowledge and compliance. The results of this study showed that respondents had good knowledge as many as 46 respondents (60%), sufficient knowledge as many as 21 respondents (28%), less knowledge as many as 9 respondents (12%). High compliance rates of 20 respondents (26%), moderate compliance of 31 respondents (41%), low compliance of 25 respondents (33%). Statistical test results were obtained by Asymp. The sig 0.000 is less than 0.05 so it can be concluded that there is a relationship between the level of knowledge and the adherence to antibiotic use.